Refugee Movements from the Sudan: An Overview Analysis - Otunnu, Ogenga (Refuge: Canada's Journal on Refugees, 1994)
Most refugees do not leave their home with a national passport in hand. Nor do theyhave prepaid tickets for their transport since they do not take national airlines orrailways when they leave their countries. They leave in acute situations and formany of them their journey is hampered by acute problems. They flee in disguise,avoid the main roads; and are ignorant of what lies ahead since they travel throughunknown territory often without guide. This makes flight for many a grope forsafety in total darkness. And such flight is filled with numerous hardships anddanger. (Bulcha, M. 1988. Flight and Integration: Causes of Mass Exodus from Ethiopia and Problemsof Integration in the Sudan. Uppsala: Scandinavian Institute of African Studies, 138.)